Hunting Nature Ivan Turgenev and the Organic World - Hodge, Thomas P. (Academic Studies Press, 2022)
In Hunting Nature, Thomas P. Hodge explores Ivan Turgenev's relationship to nature through his conception, description, and practice of hunting-the most unquenchable passion of his life. Informed by an ecocritical perspective, Hodge takes an approach that is equal parts interpretive and documentarian, grounding his observations thoroughly in Russian cultural and linguistic context and a wide range of Turgenev's fiction, poetry, correspondence, and other writings. Included within the book are some of Turgenev's important writings on nature-never previously translated into English. Turgenev, who is traditionally identified as a chronicler of Russia's ideological struggles, is presented in Hunting Nature as an expert naturalist whose intimate knowledge of flora and fauna deeply informed his view of philosophy, politics, and the role of literature in society. Ultimately, Hodge argues that we stand to learn a great deal about Turgenev's thought and complex literary technique when we read him in both cultural and environmental contexts. Hodge details how Turgenev remains mindful of the way textual detail is wedded to the organic world-the priroda that he observed, and ached for, more keenly than perhaps any other Russian writer.